2021
DOI: 10.17221/44/2021-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Negative impact of heat stress on reproduction in cows: Animal husbandry and biotechnological viewpoints: A review

Abstract: This review summarises current knowledge of the relationship between heat stress (HS) and reproduction in cattle. It focuses on research from the viewpoint of genetics (breed), from the viewpoint of reproduction physiology (in vivo and in vitro) and from the animal husbandry practice. From the viewpoint of animal husbandry, it was evidenced that heat stress influences reproduction before, during and after conception. Most publications suggest the negative impact of heat stress on the reproductive physiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
5
0
1
Order By: Relevance
“…For instance, Vinet et al [8] found that this correlation was negative for production (i.e., a stronger decline for high-yielding cows) and positive for somatic cell score (i.e., sensitive cows are even more sensitive at high THI). For reproduction, fertility has also been predicted to decline with increasing THI, e.g., [1,9,10], which is consistent with in vitro tests (reviewed in [11,12]). Heat stress is known to adversely affect different stages of cattle reproduction, suppressing the dominance of the large follicle, impairing oocyte quality and embryo development, and increasing embryo mortality (reviewed in [12]).…”
Section: Introductionsupporting
confidence: 59%
“…For instance, Vinet et al [8] found that this correlation was negative for production (i.e., a stronger decline for high-yielding cows) and positive for somatic cell score (i.e., sensitive cows are even more sensitive at high THI). For reproduction, fertility has also been predicted to decline with increasing THI, e.g., [1,9,10], which is consistent with in vitro tests (reviewed in [11,12]). Heat stress is known to adversely affect different stages of cattle reproduction, suppressing the dominance of the large follicle, impairing oocyte quality and embryo development, and increasing embryo mortality (reviewed in [12]).…”
Section: Introductionsupporting
confidence: 59%
“…Finally, the health status was studied from different points of view such as heat stress, metabolic status, semen quality etc. (Bezdicek et al 2021; Pytlik et al 2022;Stadnik et al 2022). But beyond all doubt the first task is breeding for health.…”
Section: Resultsmentioning
confidence: 99%
“…The opposite is the case in the summer months, when the days are longer and an increase in milk production is observed. Barash et al (2001) and Bezdicek et al (2021) reported an average increase of 1.2 kg in milk production for every extra hour of sunlight. They also observed a decrease in milk fat and protein in spring and an increase in autumn again.…”
Section: Discussionmentioning
confidence: 99%